„… I am capable and able for a complete renewal…”: Interview with Cepol Director, Ferenc Bánfi (Academic Journal of Internal Affairs, 2025)
This is the opening piece of a set of interviews, by dr. pol. lt. col. Richard Leyrer, JHA Counsel, aimed at familiarizing the readers with the activities of European institutions in the JHA field.
Keywords: Ferenc Bánfi; interview; Cepol